Minangkabau Language Maintenance by the Association of Sei Jaring Community in Medan - Yenita Uswar; Amrin Saragih; Tina Mariany Arifin (LINGUISTIK TERAPAN, 2014)
The objectives of this qualitative research were (1) to identify the factors that affect the Minangkabau language (ML) maintenance in Medan, (2) to discover the parents’ efforts in maintaining ML in Medan and (3) to find out the reason why the speakers have to maintain ML. The souree of data is the nembers of the Association of Sei Jaring Community (Ikatan Warga Sei Jaring: IWS) in Medan. The sample was 10 families including 10 parents and their children. The instruments of this study are a questionnaire and an interview. The questionnaire was used to answer the factors affected the maintenance of ML and how factors affected the maintenance of ML. The interview was used to discover the influence why Minangkabau’s people have to maintain ML. There are four factors in ML maintenance, the parents’ role, the role of family, the intramarriage and homeland visits. After distributing questionnaire and did some interviews it is found that IWS especially for the third generation (children) has the danger level in ML when they communicate to each other. Meanwhile, the data analysis also shows that both fathers and mothers communicate to each other with ML. This condition occurred because of the influence of the environment. Parents have to keep communication and teaching Minangkabau language continuously to their children. so, the young generation can keep the existence of ML for their future. Keywords: Minangkabau Language Maintenance, parents’ efforts, the young generation.